2001
DOI: 10.2514/2.4847
|View full text |Cite
|
Sign up to set email alerts
|

Flight Mechanics of an Elastic Symmetric Missile

Abstract: The free-flight motion of an elastic missile is approximated with three bodies connected by two massless elastic cantilever beams. If the mass distribution of the three bodies is 1-2-1, the frequency of the symmetric oscillation of the outer bodies is within 5% of the classical frequency of the oscillation of a free-free beam. A second combined pitching antisymmetric flexing motion can occur with a frequency that is almost twice that of the symmetric flexing motion. As the beam stiffness is reduced, the symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Mikhail showed examples of spin lock-in when fin damage produces a roll inducing moment sufficient to cause a steady state spin greater than the lowest elastic frequency and the initial spin rate was zero. However, Murphy and Mermagen (2000) insisted that results obtained by the former should be dismissed due to incorrect expressions for the angular momentum. Murphy and Mermagen (2000) approximated the elastic missile by three rigid bodies connected by two massless elastic beams and showed that it is impossible to cause spin lock-in by roll inducing moment and zero initial spin alone.…”
Section: Static and Dynamic Aeroelastic Instabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Mikhail showed examples of spin lock-in when fin damage produces a roll inducing moment sufficient to cause a steady state spin greater than the lowest elastic frequency and the initial spin rate was zero. However, Murphy and Mermagen (2000) insisted that results obtained by the former should be dismissed due to incorrect expressions for the angular momentum. Murphy and Mermagen (2000) approximated the elastic missile by three rigid bodies connected by two massless elastic beams and showed that it is impossible to cause spin lock-in by roll inducing moment and zero initial spin alone.…”
Section: Static and Dynamic Aeroelastic Instabilitymentioning
confidence: 99%
“…However, Murphy and Mermagen (2000) insisted that results obtained by the former should be dismissed due to incorrect expressions for the angular momentum. Murphy and Mermagen (2000) approximated the elastic missile by three rigid bodies connected by two massless elastic beams and showed that it is impossible to cause spin lock-in by roll inducing moment and zero initial spin alone. It should be noted that the use of the three-body model is a major simplification of the actual physical problem.…”
Section: Static and Dynamic Aeroelastic Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Because these projectiles have to resist very large aerodynamic loads due to their high-velocity flight at sea level, designers have been concerned about the possibility of aeroelastic deformations [1][2][3][4][5][6][7]. There is some evidence that a small number of these projectiles have been forced to spin at rates close to their lowest elastic frequency and have been subject to large inelastic deformations.…”
Section: Introductionmentioning
confidence: 99%